Persistent proteinuria among a cohort of Nigerian children with sickle cell anaemia - Angela Esohe Adeoti-Lawani; Gabriel Obiorah Ezeh; Elizabeth Eberechi Oyenusi; Chris Imokhuede Esezobor (PLoS ONE, 2026)
Background Persistent proteinuria is an early and modifiable marker of kidney damage. Although Nigeria has the highest burden of sickle cell anaemia (SCA) globally, the prevalence of proteinuria is unknown largely because many of the studies only determined proteinuria in a single urine sample or used less sensitive methods, such as dipstick. Unlike dipstick screening, quantitative urine protein-creatinine ratio allows more accurate detection of low-grade proteinuria. Objectives To determine the prevalence and determinants of persistent proteinuria among children with SCA. Methods Children with SCA and age and sex-matched controls attending a publicly funded hospital in central Nigeria were consecutively enrolled. Proteinuria was determined at the first visit using the spot urine protein creatinine ratio and repeated at least 3 months afterwards for those with proteinuria. In addition, serum creatinine, full blood count, and fetal hemoglobin were determined at the first visit. Persistent proteinuria was defined as a urine protein-to-creatinine ratio ≥0.2 at both visits over a follow-up period of at least 3 months. Participants were classified based on the presence or absence of persistent proteinuria, and baseline characteristics were compared using within-group distributions for categorical variables with appropriate statistical tests. Results One hundred and forty-nine children, each with SCA and controls, were enrolled, respectively. The median (IQR) age of the study participants was 9.0 (6.0) years for both groups, with 65% being males. Persistent proteinuria occurred in 35 (23.5%) children with SCA versus 4 (2.7%) controls (p-value < 0.01). Children with persistent proteinuria had a lower level of fetal hemoglobin. (adjusted OR 0.583, 95% C.I 0.473–0.719). Conclusion About a quarter of children with SCA had persistent proteinuria, an early and modifiable marker of chronic kidney disease.